ADCYAP1 as a pan-solid cancer biomarker: predictor of immunotherapy efficacy in bladder cancer and prognostic potential across solid tumors - Xiaoyu Jing; Ying Deng (Discover Oncology)
Abstract Background ADCYAP1 has been identified with potential effects ranging from tumor growth activation to inhibition. However, it remains unknown whether ADCYAP1 plays a substantial role across pan-cancer. Methods The potential roles of ADCYAP1 in 33 different tumors were analyzed based on The Cancer Genome Atlas (TCGA). We investigated the expression levels, mutations, survival rates, DNA methylation, and immune cell infiltration associated with ADCYAP1. In addition, we analyzed immunotherapy response data from the Tumor Immunotherapy Gene Expression Resource (TIGER) database and previously reported studies. Results In general, high expression of ADCYAP1 has been linked to poor OS in the TCGA Bladder urothelial carcinoma cohort (BLCA) (p = 0.003), Stomach adenocarcinoma (STAD) cohort (p = 0.002), and Uterine corpus endometrial carcinoma (UCEC) cohort (p = 0.032). However, the opposite association was observed in the Adrenocortical carcinoma (ACC) cohort (p = 0.034), Kidney renal clear cell carcinoma (KIRC) cohort (p < 0.0001), and Liver hepatocellular carcinoma (LIHC) cohort (p = 0.027). Notably, the BLCA and UCEC samples showed a higher frequency of ADCYAP1 mutations compared to others. Our results suggested that the level of ADCYAP1 methylation can serve as a prognostic factor for OS in patients with STAD and UCEC. The analysis of six cancer immunotherapy(CIT) response datasets showed that ADCYAP1 has predictive value for immunotherapy response in BLCA. Conclusions There is a potential correlation between ADCYAP1 and tumor immunity. Consequently, we propose that ADCYAP1 could potentially serve as a valuable prognostic biomarker for BLCA.